1985
DOI: 10.1002/jlb.37.5.493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on the Functions of Human Polymorphonuclear Leukocytes In Vitro

Abstract: Effects of nicotine on migration, extracellular release of lysosomal enzymes, and superoxide anion (O-2) production of human polymorphonuclear leukocytes (PMN) were studied. Nicotine (5 X 10(-6) to 5 X 10(-4) M) had no effect on random migration, chemotaxis to fMet-Leu-Phe, nor on chemokinesis induced by fMet-Leu-Phe. Nicotine, however, inhibited both extracellular release of lysosomal enzymes from PMN and O-2 production of PMN, both of which were induced by fMet-Leu-Phe and cytochalasin B. The inhibition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
5
35
0
1
Order By: Relevance
“…The non-volatile component did not inhibit migration. Nicotine had no effect on PMN migration and chemotaxis (Sasagawa et al, 1985). Macrophages from the lungs of smokers have a greater inhibitory effect on lymphocyte proliferation than macrophages from the lungs of nonsmokers.…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 81%
“…The non-volatile component did not inhibit migration. Nicotine had no effect on PMN migration and chemotaxis (Sasagawa et al, 1985). Macrophages from the lungs of smokers have a greater inhibitory effect on lymphocyte proliferation than macrophages from the lungs of nonsmokers.…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 81%
“…The importance of nAChR-coupled signaling pathways for the physiologic regulation of the subcellular machinery of crawling locomotion has been underscored by the results of the studies involving different cell types. Interestingly, both stimulatory (Dwivedi and Long, 1989;Grando et al, 1995;Yong et al, 1997) and inhibitory ( Owen and Bird, 1995;Thomas et al, 1981;Zia et al, 2000) effects have been reported, as have lack of effects (Drell et al, 2003;Grando et al, 1993a;Sasagawa et al, 1985), suggesting that either different cells express different combinations of cell surface receptors to ACh and/or in different cells the same types of ACh receptors are coupled to different signaling pathways. The reports of lack of effects of ACh and its congeners on migration suggested that one type of ACh receptors stimulates and another inhibits migration and that simultaneous activation of both groups of the receptors in a single cells results in a zero net effect on motility.…”
Section: Discussionmentioning
confidence: 99%
“…This factor is mainly produced by haematopoietic cells, and influences the proliferation, survival, maturation and functional activation of cells of the neutrophilic granulocyte lineage (19). Chronic cigarette smoking is associated with functional depression (20) and an increased blood count (21) of neutrophils. Tobacco smoking also causes an increased production of TNF-a (22) and high serum G-CSF levels (23).…”
mentioning
confidence: 99%